Building International Cooperation to Leverge Global Competitiveness - Lely Verawati Br. Marbun (LPPM IAKN Tarutung, 2022)
International relation is very much needed in the current of globalization era, why should that? Because with the existence of international cooperation involving two or more countries, the level of prosperity and peace will be more maintained. The effects of this alliance or cooperation usually cover several fields, such as: politics, security, economy, education and others. With this international cooperation, a country that has strength in a certain field will certainly protect the other allied countries who may be in trouble. So basically this international cooperation relationship is like a symbiotic mutualism which is benefits both sides in various fields that they agree on.